1998
DOI: 10.1097/00001756-199802160-00028
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized lipoproteins activate NF-κB binding activity and apoptosis in PC12 cells

Abstract: Oxidative stress in the central nervous system may cause oxidation of lipoproteins. The oxidized lipoproteins may in turn damage cellular and subcellular membranes and other biomolecules, leading to tissue injury and cell death. Recently, we have demonstrated that oxidized LDL and VLDL induced cell death in a dose-dependent manner. The present study examined the possible signal transduction cascade leading to cell death by oxLDL and oxVLDL in PC12 cells. Using the electrophoretic mobility shift assay, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 8 publications
3
38
0
Order By: Relevance
“…The first evidence of resveratrol affecting NF-B was obtained by Draczynska-Lusiak et al (8). They demonstrated that oxidized lowdensity lipoprotein treatment activates NF-B in PC12 cells and that resveratrol attenuates the activation (8). Thereafter, there were many reports of resveratrol suppressing NF-B activation in a variety of cell lines, including U-937, Jurkat, and HeLa cells, induced by several agents, including 12-O-tetradecanoylphorbol-13-acetate, lipopolysaccharide, H 2 O 2 , and ceramide (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first evidence of resveratrol affecting NF-B was obtained by Draczynska-Lusiak et al (8). They demonstrated that oxidized lowdensity lipoprotein treatment activates NF-B in PC12 cells and that resveratrol attenuates the activation (8). Thereafter, there were many reports of resveratrol suppressing NF-B activation in a variety of cell lines, including U-937, Jurkat, and HeLa cells, induced by several agents, including 12-O-tetradecanoylphorbol-13-acetate, lipopolysaccharide, H 2 O 2 , and ceramide (4).…”
Section: Discussionmentioning
confidence: 99%
“…4 and 5). The first evidence of resveratrol affecting NF-B was obtained by Draczynska-Lusiak et al (8). They demonstrated that oxidized lowdensity lipoprotein treatment activates NF-B in PC12 cells and that resveratrol attenuates the activation (8).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, resveratrol was found to be a highly potent antioxidant that could inhibit free radical generation in the brain, spinal cord, heart, kidney, liver, red cell membrane, and so on [19,36,[44][45][46][47][48][49] . It has been shown that it inhibits lipid peroxidation [50] , and prevents apoptotic cell death induced by oxidative stress [51,52] . It has been postulated that resveratrol could supress mitochondria-induced production of ROS in rat brain [53] , protect DNA from oxidative damage in stroke-prone hypertensive rats [54] , and could inhibit neuronal loss after ischemia/reperfusion injury in gerbils [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis contributes to plaque instability, rupture and thrombus formation (61). Although it has not been proven in a vascular system, RSV (50 ìM) blocks apoptosis induced by oxidized VLDL and LDL in PC12 cells (21), and its antiapoptotic activity has been shown to depend on the direct inhibition of the main arachidonate metabolizing enzymes (58).…”
Section: Inhibition Of Ldl Oxidationmentioning
confidence: 99%